Strategi Komunikasi dalam Mempertahankan Minat Pendengar melalui Media Sosial pada Program ‘Big City Beatz’ Motion Radio 97,5 Fm - Fariz Fajri Bagaskara; Sigit Pramono Hadi (Bandung Conference Series: Communication Management, 2023)
Abstract. The Big City Beatz program is a hip-hop Rnb music broadcast program on Motion Radio 97.5 FM Jakarta. As a Hiphop RnB music program, the habit of listening to the radio on the go (in vehicles) has decreased due to restrictions on community activities, making the Big City Beatz program experience obstacles in interacting with social media activities. Various ways and strategies are used by the social media team to interact with listeners through social media. The Big City Beatz social media team is working hard so that the content presented to listeners through social media can be conveyed and has good responses by listeners. Motion Radio is a radio station that carries the Rnb hip-hop music genre. This research was conducted with the aim of knowing Big City Beatz's social media strategy to maintain listeners' interest through social media and to find out the obstacles farmers experience while processing social media content. This study used a qualitative research approach with descriptive analysis methods and research data collection techniques were conducted using in-depth interviews. The results of this study were strengthened by the data on Big City Beatz social media ratings that researchers obtained from Motion Radio. The conclusion and results of this study are that the social media program strategy carried out by Big City Beatz is to provide the latest social media content and broadcast it on social media to find out the response from listeners. Abstrak. Program Big City Beatz merupakan program siaran music hiphop Rnb di Motion Radio 97.5 FM Jakarta. Sebagai program music Hiphop RnB, kebiasaan mendengarkan radio di perjalanan (di kendaraan) yg berkurang karena pembatasan kegiatan masyarakat, membuat program Big City Beatz mengalami hambatan dalam interaksi aktivitas media sosial. Berbagai cara dan strategi dilakukan tim media sosial untuk berinteraksi kepada pendengar melalui media sosial. Tim media sosial Big City Beatz berusaha keras agar konten yang disajikan kepada pendengar melalui media sosial, dapat tersampaikan dan memiliki tanggapan yang baik oleh pendengar. Motion Radio merupakan stasiun radio yang mengusung genre music hiphop Rnb. Penelitian ini dilakukan dengan tujuan mengetahui strategi media sosial Big City Beatz untuk mempertahankan minat pendengar melalui media sosial dan untuk mengetahui hambatan hambatan yang dialami selama melakukan proses konten media sosial. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan metode analisis deskriptif dan teknik pengumpulan data penelitian dilakukan dengan metode wawancara yang mendalam. Hasil dari penelitian ini diperkuat denganiadanyaidata tanggaan media sosial Big City Beatz yang penulis peroleh dari Motion Radio. Kesimpulan dan hasil dari penelitian ini adalah strategi program media sosial yang dilakukan oleh Big City Beatz adalah memberikan konten media sosial terbaru dan ditayangkan di media sosial untuk mengetahui tanggapan dari para pendengar.